ORGANIC FARMING IN AN ORGANIC PRODUCT INSTALLATION - Rahmina Mamash gizi Zamanova (Foundations and Trends in Modern Learning, 2023)
The most global problem in the world is to preserve soil and vegetation for future generations by using nature and its resources efficiently. Over thousands of years, as the society developed, its needs also increased, the more the volume of needs increased, the more natural resources decreased. The complete violation of the natural balance between society and nature - the reduction of vegetation cover, the destruction of fauna and flora, the drying up of rivers, desertification, the release of millions of tons of carbon dioxide into the air and the lack of greenery that cannot absorb this carbon, the degradation of 52% of arable land in the world due to various reasons is modern. has put a person in front of difficult facts and incurable diseases. If this attitude continues, in the next 40-50 years, modern civilization will end and the development of the human race may stop! Globally, the annual loss of fertile soil from cropland is 75 billion tons, which means a loss of agricultural products worth USD 400 billion annually. Land degradation affects the nutrition of 1.5 billion people per capita. Since 1960, when the mass application of chemical fertilizers and pesticides to agriculture began, people have tried to get the maximum yield by using large quantities of these chemical fertilizers and pesticides. However, the toxic substances (nitrate, nitrite, pesticide residues) collected in the products obtained by technological methods seriously damage people's health and expose people to incurable diseases. Scientists have determined that a pesticide applied to the soil to kill 1 pest kills 1,700 beneficial organisms living in the soil. Millions of tons of N, P, K fertilizers are applied to the soil every year, so that 40-45% of each 100% nitrogen fertilizer applied is collected in the air and 20-25% in groundwater and water bodies. 20-25% of the nitrogen taken by the plant cannot be completely digested by the plant, and its residues are converted into nitrous compounds, which causes the formation of cancer in the human body. The P2O5 active ingredient in the superphosphate given to the soil is 19%. The remaining 81% are additives and heavy metals that even industry cannot clean. Heavy metals in 1 kg of simple superphosphate fertilizer Ca (H2PO4)2: Ar-1,2-2,2; Ca 50-70; Cr 66-243; Co 0-9; Pb is 7-92 mg. However, the permissible limit for cereal crops alone is 0.02 g. In recent years, diseases that have increased rapidly and reached the level of a pandemic make people think more: Why can't we protect our loved ones from such diseases?